ANALYZING ORGANIZATIONAL COMMITMENT IN BANKING: THE IMPACT OF WORK-LIFE BALANCE, ORGANIZATIONAL SUPPORT, AND OPERATIONAL WORKLOAD - Aziz Asri Mufti; Suarmanayasa I Nengah; Telagawathi Ni Luh Wayan Sayang (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This research aims to analyse the influence of work-life balance, perceived organizational support, and workload on organizational commitment at PT. Bank Rakyat Indonesia (Persero) Tbk., Gatot Subroto Branch Office, Denpasar. The study employed a quantitative causal research design to examine the relationships between these variables. A census sampling technique was utilized, involving the entire population of 133 permanent employees. Data were collected through structured questionnaires using a 5-point Likert scale and analysed using multiple linear regression, partial t-tests, and simultaneous F-test via SPSS 25. The results demonstrate that work-life balance and perceived organizational support each have a positive and significant partial effect on organizational commitment. Conversely, workload has a negative and significant influence, indicating that excessive task demands can drastically reduce employee loyalty. Simultaneously, these three variables significantly influence commitment with an F-value of 163.809 (p < 0.05), accounting for 79.2% of the commitment variance. This study provides a significant contribution by validating